The experiences of learner nurses regarding clinical placement during the coronavirus disease 2019 pandemic at the University of Limpopo - Nchabeleng, Linda (My University, 2023)
Academic nursing programme during the COVID-19 pandemic has been affected, as students had to be withdrawn from clinical experiential learning. This led to learner nurses having challenges in completing their clinical hours required by the South African Nursing Council training requirements. The study aimed to explore and describe the challenges experienced by learner nurses regarding clinical placement during the COVID-19 pandemic at the University of Limpopo. Method: A qualitative, descriptive, and explorative research method was used to explore the experiences of learner nurses regarding clinical placement during the COVID-19 pandemic at the University of Limpopo. A non-probability purposive sampling method was used to select participants. The population included 204 undergraduate learner nurses enrolled at the University of Limpopo to study Bachelor of Nursing degree for the academic year 2021. Data was collected through focus group interviews which consisted of eight to twelve learner nurses in each group. Six focus group interviews were conducted to collect data. Data were analyzed following Tesch`s open coding method. The measures to ensure trustworthiness namely credibility, transferability, confirmability, and dependability were followed. Results: The following themes emerged during data analysis; The impact of COVID19 on the clinical placement of learner nurses, restricted exposure to the clinical area during a hard lockdown, the effects of COVID-19 on the mental well-being of learner nurses and the learner nurses’ support, and recommendations. Additionally, the following sub-themes also emerged during data analysis; Incompetence in the performance of some skills, compromised integration of theory to practice, Inadequate clinical hours as required by SANC, lack of personal protective clothing at the clinical areas, exposure to COVID-19 risk, fear of COVID-19 Infection, fear of patients, Inadequate support from preceptors, Inadequate supervision by the senior personnel at the clinical area, difficulties to cope, personal and social coping strategies, educational institution support for learner nurses, management of clinical learning and clinical hours, preparation, protection, and support during clinical practice and the provision of resources and compensation. Conclusion: Nursing education institutions should ensure that learner nurses get clinical exposure even during a pandemic. The study further recommends that nursing v education institutions procure good quality and sufficient personal protective equipment for the learner nurses and that professional nurses at the accredited clinical facilities should assist the learner nurses in correlating theory with practice during the COVID-19 pandemic by supervising them during their clinical training.
Thesis (M.A. (Nursing)) -- University of Limpopo, 2023
Keywords: Clinical placement; Covid-19; Experience; Learner nurses; Pandemic; COVID-19 (Disease); COVID-19 Pandemic, 2020-; Nursing students; Personal protective equipment; Nursing -- Study and teaching